Raising perinatally infected children: reflections from HIV-positive adolescents and young people and their guardians in Cape Town, South Africa - Mokganyetji, Tebogo (Department of Public Health and Family Medicine, 2023)
There is an increase in the number of adolescents and young people who are growing up with HIV across the globe. These adolescents and young people are transitioning into adulthood with the pandemic, which necessitates research on the experiences of growing up with HIV and how caregivers manage raising these children. This study explored experiences of adolescents and young people living with HIV by examining the context of growing up with HIV, how caregivers manage raising HIV positive adolescents and young people and the overall management of paediatric HIV. The research investigated a) how adolescents and young people experience the process of HIV disclosure; b) the experiences of adolescents and young people and caregivers with the different healing systems i.e., biomedical, religious, and traditional healing systems; c) how adolescents and young people and caregivers navigate, experience, and manage living with HIV as a chronic illness; and d) some of the key social and cultural practices and contexts that HIVpositive adolescents and young people and their caregivers must negotiate in managing HIV infection. This research was conducted in Khayelitsha Township in Cape Town. Different stakeholders who work on paediatric HIV Khayelitsha were purposively and conveniently sampled to participate in the research. Furthermore, adolescents and young people between the ages of 14 – 24, who were vertically infected and whose HIV status has been fully disclosed and their caregivers participated in the research. Qualitative methods including participant observation, semi-structured interviews were conducted, and participatory research methods including the River of Life maps and Vision Boards and WhatsApp were used. The study design used a mini-ethnographic, longitudinal study which included action research, used a grounded theory approach to interview and conduct the analysis. The data was transcribed analysed thematically to understand the patterns of the emerging data. A further analysis was conducted using NVivo QSR software. The research findings highlight the importance of understanding the complex biomedical, social, and cultural components of HIV and how those intersect with social contexts of raising HIV positive adolescents and young people. The thesis documents the significance of disclosure of HIV status to adolescents and young people as a starting point to retaining them in care. The process of disclosure is noted as complex for the adolescents and young people, their caregivers and for the different people they have relationships with including their extended families, friends, partners, communities, and their schools. This research also maps out the day-to-day experiences of adolescents and young people who know they are growing up with HIV to understand their social context. This social context explores the different facets of life that these adolescents and young people navigate as they seek to make sense of their lives while growing up with HIV. Furthermore, this thesis documents the different ways in which communities understand the concept of healing and health, and how these concepts intersect. The research the points at which the different belief systems interact with how people understand being healthy and the interplay between the biomedical, traditional, and spiritual understandings of being healthy. People's engagement with the different systems of healing are important for HIV management. Participants also created vignettes illustrating their river of lives journey and vision boards depicting their dreams and aspirations. Key recommendations were made about how to further understand the different facets of HIV and how a holistic public health approach that is tailored for adolescents and young people growing up with HIV can facilitate improved HIV management.